A scalability analysis of grid allocation mechanisms - Michael Reinicke; Werner Streitberger; Torsten Eymann (Universität Bayreuth, Lehrstuhl für Wirtschaftsinformatik, 2008)
This article examines the broker's behavior with regard to a varying number of participating nodes and shows that incremental losses have to be accepted in central resource allocation when introducing new nodes.
urn:nbn:de:bvb:703-opus-3875
Keywords: 650; Grid Computing